Mixed Cryoglobulinemia as a Potential Indicator of Clinically Silent Hepatitis C Infection (Translation: The University of Toledo Journal of Medical Sciences, 2024)
Hepatitis C virus (HCV) is one of the major causes of chronic liver disease and its prevalence is increasing worldwide. There are many extra hepatic manifestations of Hepatitis C infection including B –cell lymphoproliferative disorders. Mixed cryoglobulinemia (MC) is the most common prototype of B-cell lymphoproliferative disorders. Cryoglobulinemia is an immune complex mediated disease causing multi organ damage with vasculitis being the primary manifestation. We report a case of 50 years old Asian lady having clinically silent chronic liver disease secondary to hepatitis C who presented to us with a purpuric skin rash, joint pains and fatigue. She was confirmed to be a case of mixed cryoglobulinemia. Patient was prescribed direct antiviral agents and prednisolone which improved her condition to a great extent. Heightened awareness of cutaneous manifestations of MC associated with HCV might improve the detection rate of clinically silent HCV infection.
Keywords: Cryoglobulinemia; chronic liver disease; vasculitis; Hepatitis C